2010
DOI: 10.3109/14756360903389906
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and biological properties of triazole derived compounds and their transition metal complexes

Abstract: Triazole derived Schiff bases and their metal complexes (cobalt(II), copper(II), nickel(II), and zinc(II)) have been prepared and characterized using IR, (1)H and (13)C NMR, mass spectrometry, magnetic susceptibility and conductivity measurements, and CHN analysis data. The structure of L(2), N-[(5-methylthiophen-2-yl)methylidene]-1H-1,2,4-triazol-3-amine, has also been determined by the X-ray diffraction method. All the metal(II) complexes showed octahedral geometry except the copper(II) complexes, which show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“…The molar conductance of all the metal(II) complexes ( 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ) was observed at room temperature in DMF as a solvent and their results in (Ω −1 cm 2 mol −1 ) are recorded in Table . The molar conductance values of all the metal complexes at room temperature fall into the higher range (79.9–91.0 Ω −1 cm 2 mol −1 ) assigned to their electrolytic nature . The observed magnetic moment values of Co(II) complexes were found in the range 4.37–4.58 BM as high spin and suggested three unpaired electrons in an octahedral environment.…”
Section: Resultsmentioning
confidence: 99%
“…The molar conductance of all the metal(II) complexes ( 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ) was observed at room temperature in DMF as a solvent and their results in (Ω −1 cm 2 mol −1 ) are recorded in Table . The molar conductance values of all the metal complexes at room temperature fall into the higher range (79.9–91.0 Ω −1 cm 2 mol −1 ) assigned to their electrolytic nature . The observed magnetic moment values of Co(II) complexes were found in the range 4.37–4.58 BM as high spin and suggested three unpaired electrons in an octahedral environment.…”
Section: Resultsmentioning
confidence: 99%
“…The Schiff bases are characterized by an imine group and are formed as a condensation product 2 of primary amine with an aldehyde or ketone in the presence of a dehydrating agent such as MgSO 4 . A number of Schiff's base metal complexes have displayed bioactivity as antibacterial 3,4 , antifungal 5 , anticancer 6,7,8 , anti-inflammatory 9 , anticonvulsant 10 , antiviral 11 and analgesic 12 agents. Although metal-based ethanolamines have historically been subjected of many investigations 13,14 due to their use as buffers 15 , catalysts 16 , inhibitors 17 , ion exchangers 18 , electroplating and dyes 19 , now they are garnering attention for their biological 20 role in plant growth 21 regulation, bacterial and fungal metabolism and as a cytotoxic agent 22 .…”
Section: Introductionmentioning
confidence: 99%
“…The average activity data showed that the metal(II) complexes exhibited greater average activity (43.6%) than the average activity of the ligands (40.8%). It is therefore, concluded that the antifungal activity of the ligands increased 41,42 upon chelation/coordination with the metal ions. The comparative activity data of the ligands and their metal(II) complexes is presented in Figure 4.…”
Section: In Vitro Antifungal Bioassaymentioning
confidence: 99%